THE COLLABORATION BETWEEN THE PEDAGOGUE AND TEACHERS IN THE FUNCTION OF IMPROVING THE TEACHING WORK - Gacov, Sanja (International Scientific Journal Vision, 2023)
Education is one of the most promising areas in life. The student who will start his education in the first grade of primary school in 2022 will reach the peak of his professional activity in the forties of the 21st century. Therefore, the school does not prepare students for the world "today", but for the one "tomorrow", which is difficult to even imagine. But if humanity wants to survive, it has to deal with problems that will be solved by the student who is now sitting in the school desk. The work of the school pedagogue has fundamental importance in the functioning of the educational process and no other educational and professional profile of a school worker can replace the work and function of the school pedagogue in schools. In this paper, we put a special emphasis on the part in which we explain in more detail the entire work methodology of the school pedagogue, specifically in the elementary school. In this section, we elaborate the following areas of the school pedagogues work individually: planning, programming and evaluation of educational work; instructional - pedagogical work of the school pedagogue with the teachers; the school pedagogue work with students; the cooperation of the pedagogue with the parents; analytical-research work of the school pedagogue; cooperation of the school pedagogue with other professional bodies and social institutions. In this paper, we will try to explain the essential need for cooperation between the school pedagogue and the teachers in order to improve the teaching work. This scientific paper is of essential importance and will make a great contribution to education and science in general.